Finding Dory - Crockford, Samantha (Parragon Books, 2016)
Forgetful Dory is very happy living in the ocean with her friends, Marlin and Nemo. But one day, memories of her long-lost parents come flooding back to her. With the help of old friends and new, including Hank the septopus, Dory tries to discover her past